2021
DOI: 10.1002/jgc4.1537
|View full text |Cite
|
Sign up to set email alerts
|

A report of the AGCPD task force to evaluate associations between select admissions requirements, demographics, and performance on ABGC certification examination

Abstract: Graduation from a genetic counseling graduate program accredited by the Accreditation Council of Genetic Counseling and certification obtained by passing the American Board of Genetic Counseling (ABGC) certification examination are increasingly required to practice as a genetic counselor in the USA. Despite the ABGC certification examination serving as a gateway to the genetic counseling career, there have been no research studies to date that have examined what variables are associated with examination perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(58 reference statements)
0
10
1
Order By: Relevance
“…In the present study, admissions committee members viewed the need to take the GRE as significantly less of a barrier when compared with prospective applicants. While it has been suggested that the continued requirement of the GRE as part of the application process has led to selection against underrepresented minority students (Myers et al, 2021), our study found that admissions committee members did not perceive the GRE requirement to be a significant barrier for prospective students in applying to genetic counseling programs. It is important to note that the GRE is not required for entry into any of the Canadian genetic counseling programs and thus perhaps not viewed as a barrier by Canadian admissions committee members.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the present study, admissions committee members viewed the need to take the GRE as significantly less of a barrier when compared with prospective applicants. While it has been suggested that the continued requirement of the GRE as part of the application process has led to selection against underrepresented minority students (Myers et al, 2021), our study found that admissions committee members did not perceive the GRE requirement to be a significant barrier for prospective students in applying to genetic counseling programs. It is important to note that the GRE is not required for entry into any of the Canadian genetic counseling programs and thus perhaps not viewed as a barrier by Canadian admissions committee members.…”
Section: Discussioncontrasting
confidence: 71%
“…As of 2022, there were 57 accredited Master's in genetic counseling programs in North America admitting a total of 547 students (Association of Genetic Counseling Program Directors, 2022). Individual programs have their own application requirements however, the current application process for North American genetic counseling Master's degree programs typically involves submission of a written biographical statement, assessment of academic performance with prerequisite courses in sciences, statistics, genetics and psychology, volunteer/advocacy experience, and efforts to gain exposure to the profession and reference letters, all of which are reviewed by an admissions committee (Myers et al, 2021). Programs then interview a select number of applicants and following the interviews, admissions committee members rank applicants as part of a Match process.…”
mentioning
confidence: 99%
“…In a recent original research article in this journal, Myers et al reported findings supporting the widely held assumption that white female trainees have higher odds of passing the American Board of Genetic Counseling (ABGC) certification examination on their first attempt than their non-female non-white peers (Myers et al, 2021).…”
mentioning
confidence: 87%
“…While there are published studies describing remediation practices in medical education, there is limited information available regarding remediation practices in genetic counseling training programs. A recent study assessed associations between genetic counselor trainee progress and first-time certification examination performance (Myers et al, 2022) remediation, and 2.6% required remediation for professionalism. For first-time certification examination takers, the need for clinical, professional, or academic remediation was associated with a decreased pass rate compared to students not needing remediation (65% vs. 90%).…”
mentioning
confidence: 99%